Analysis of Interaction and Flow Pattern of Multiple Bubbles in Shear-Thinning Viscoelastic Fluids - Hongbin He; Zhuang Liu; Jingbo Ji; Shaobai Li (Energies, 2023)
A numerical study was conducted on the interaction of bubbles with different diameters and arrangements in shear-thinning viscoelastic fluids using OpenFOAM. The Volume of Fluid (VOF) method combined with the surface tension model was used to track the gas–liquid interface, and the rheological properties of the fluid were characterized with the Giesekus model. The numerical results are corresponded with the previous references, verifying the correctness of the simulation method. The influences of the initial bubble diameter, horizontal spacing, and arrangement on the motion state of three parallel bubbles were studied in detail. The flow pattern of the bubble rising was analyzed and compared with the motion state of parallel unequal double bubbles. As the diameter of the bubbles increases, the interaction among three equal size bubbles is changed from coalescence to detachment. Changing the diameter of one of the bubbles will significantly affect the movement of the larger diameter bubble, which is due to the enhancement in kinetic energy. The final state of some arrangement ways is consistent with the phenomenon of unequal double bubbles. The shear thinning effect, the velocity difference between bubbles, and the flow field around bubbles are considered the main reasons that decide the interaction between bubbles.